2019
DOI: 10.1109/access.2019.2947992
|View full text |Cite
|
Sign up to set email alerts
|

On the Feasibility of 5G Slice Resource Allocation With Spectral Efficiency: A Probabilistic Characterization

Abstract: An important concern that 5G networks face is supporting a wide range of services and use cases with heterogeneous requirements. Radio access network (RAN) slices, understood as isolated virtual networks that share a common infrastructure, are a possible answer to this very demanding scenario and enable virtual operators to provide differentiated services over independent logical entities. This article addresses the feasibility of forming 5G slices, answering the question of whether the available capacity (res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 74 publications
(90 reference statements)
0
7
0
Order By: Relevance
“…The results showed that complete centralized process and management and efficient energy utilization of structure in a short amount of traffic time were accomplished by turning off data RRHS. The authors of [ 127 ] presented the probabilistic characterization of the feasibility of 5G slice resource allocation issues to determine whether or not they could be addressed. They presented a mini slot-based slicing allocation (MISA), which is a unique spectral-efficient scheme to assign PRBs for the URLLC and eMBB service-based utilization of mini-slots.…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that complete centralized process and management and efficient energy utilization of structure in a short amount of traffic time were accomplished by turning off data RRHS. The authors of [ 127 ] presented the probabilistic characterization of the feasibility of 5G slice resource allocation issues to determine whether or not they could be addressed. They presented a mini slot-based slicing allocation (MISA), which is a unique spectral-efficient scheme to assign PRBs for the URLLC and eMBB service-based utilization of mini-slots.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to providing vertical slices (for vertical industries), NS may be used to generate horizontal slices which aim to improve the performance of User Equipment (UE) and enhance the user experience [92]. Although initially proposed for the partition of Core Networks (CN), using techniques such as Network Function Virtualization (NFV) and Software Defined Networking (SDN) [93], the concept of NS has been extended to provide efficient end-to-end data services by slicing radio resources in Radio Access Networks (RANs) as well [94], [95]. The slicing of radio resources mainly involves dynamic allocation of time and frequency resources based on the characteristics of multiple data services.…”
Section: F Network Slicing Based Ramentioning
confidence: 99%
“…For these three BWPs, the number of contiguous PRBs is N RB = {106, 24, 11}, respectively. In particular, a large number of PRBs is suitable for eMBB traffic flows with moderate requirements of reliability and latency [60]. Therefore, eMBB services are configured with small subcarrier spacings corresponding to numerologies µ = {0, 1} for x = 1 and x = 2, respectively.…”
Section: B Transmission Modelmentioning
confidence: 99%